KNOWLEDGE, PERCEPTION AND INVOLVEMENT OF ISLAMIC RELIGIOUS LEADERS IN HIV/AIDS PREVENTION IN IBADAN NORTH LOCAL GOVERNMENT AREA, NIGERIA (2013)
Religious leaders are potential change agents for HIV/AIDS prevention activities in their communities. Previous studies on the role of religious leaders in HIV Prevention in Nigeria have focused more on Christian religious leaders. Not enough is known about the HIV Prevention efforts of Islamic religious leaders. This study was therefore designed to assess Islamic religious leaders’ (IRLs) knowledge, perception and involvement in HIV/AIDS prevention education in Ibadan North Local Government Area (LGA), Nigeria. The cross-sectional study involved 427 IRLs selected from Mosques and Faith-Based Organizations (FBOs) in the LGA through a 3-stage random sampling technique. A validated semi-structured questionnaire which included questions on perception, level of involvement and a 15-point knowledge scale was used. Data were analyzed using descriptive statistics, t- test, Chi-square and logistic regression. Knowledge scores of 2-7, 8-10 and 11-15 were rated as poor, fair and good respectively. Level of significance was set at 0.05. Respondents’ mean age was 49.6 ± 16.0 years and 96% were males. All had heard about AIDS and their main source of information was the mass media (98.4%). Respondents’ mean knowledge score was 9.1 ± 2.3. Respondents with poor, fair and good knowledge were 26.7%, 51.3% and 22.0% respectively. Many respondents (56.2%) could not correctly identify HIV as the causative agent of AIDS. Knowledge about abstinence from pre- and extra- marital sex as a means of prevention was high (96.5%) and 98.1% perceived that HIV/AIDS is a threat to societal well-being. The opinion of 51.3% was that Muslims were as vulnerable to HIV infection as other religious groups. Most respondents (97.4%) were of the view that IRLs have important roles to play in prevention of HIV infection. Only 8.2% had ever attended training on HIV/AIDS and 22.2% had ever preached about HIV/AIDS-related issues to their congregations. Eighty percent of respondents who had preached on HIV had not had any training on HIV. Only 4.4% of leaders had ever organized HIV/AIDS-related educational activities such as seminars/workshops (80%) and awareness campaign (15%) in their mosques/FBOs. Religious leaders in mosques used for daily prayers only and those in mosques used for Friday prayers were six times (OR=0.182; 95%CI=0.054-0.608) and nine times (OR=0.103; 95%CI=0.019-0.567) less likely to organize HIV/AIDS educational programme compared with their counterparts in FBOs. The major barriers against implementing such programmes were lack of knowledge (25.1%) and lack of access to educational material (12.6%). Most respondents (94.1%) were of the view that religious leaders need basic HIV/AIDS knowledge to effectively educate their congregations and 95.6% were willing to be formally trained on HIV/AIDS. Suggestions for effective engagement of IRLs in HIV prevention included providing capacity building opportunities (30.4%) and education materials (31.9%). Knowledge and perception of HIV/AIDS among the IRLs was fair. However, majority were not involved in HIV/AIDS prevention education programmes. Formal training by health workers, advocacy and technical supports are needed to address this challenge.